Impact of an exercise program on acylcarnitines in obesity: a prospective controlled study - Rodríguez Gutiérrez, René; Lavalle González, Fernando Javier; Martínez Garza, Laura Elia; Landeros Olvera, Erick Alberto; López Alvarenga, Juan Carlos; Torres Sepúlveda, María del Rosario; González González, José Gerardo; Mancillas Adame, Leonardo Guadalupe; Salazar González, Bertha Cecilia; Villarreal Pérez, Jesús Zacarías (2012)
Background: Acylcarnitine (AC) transport dysfunction into the mitochondrial matrix is one of the pathophysiological mechanisms of type 2 diabetes mellitus (DM). The effect of an aerobic exercise (AE) program on this condition in obese subjects without DM is unclear. Methods: A prospective, randomized, longitudinal, interventional study in a University Research Center involved a 10-week AE program in 32 women without DM and a body mass index (BMI) greater than 27 kg/m2 . (Cases n = 17; Controls n = 15). The primary objective was to evaluate the influence of a controlled AE program on beta-oxidation according to modifications in short, medium, and long-chain ACs. Secondary objectives were to define the behavior of amino acids, and the correlation between these modifications with metabolic and anthropometric markers. Results: The proportion of dropouts was 17% and 6% in controls and cases, respectively. In cases there was a significant reduction in total carnitine (30.40 [95% CI 28.2 to 35.6]) vs. (29.4 [CI 95% 25.1 to 31.7]) p = 0.0008 and longchain AC C14 (0.06 [95% CI 0.05 to 0.08]) vs. (0.05 [95% CI 0.05 to 0.09]) p = 0.005 and in C18 (0.31 [95% CI 0.27 to 0.45]) vs. (0.28 [95% CI 0.22 to 0.32]) p = 0.03. Free fatty acid levels remained without change during the study in both groups. Conclusion: In conclusion, a controlled 10-week AE program improved beta-oxidation by reducing long-chain ACs. This finding highlights the importance that AE might have in avoiding or reverting lipotoxicity, and in consequence, improving insulin sensitivity and pancreatic beta cell functional reserve.